ISLAMIC EDUCATION MODEL ORIENTED ON THE VIEWS OF ACEH ULAMA ON CUSTOM SANCTIONS FOR COMMUNITIES FOR VIOLATION OF QANUN JINAYAT IN THE DISTRICT ACEH TAMIANG - Musthafa Musthafa; Asmuni Asmuni; Zainul Fuad (Edukasi Islami : Jurnal Pendidikan Islam, 2022)
This research looks at what Acehnese scholars think about the customary punishments for people who break the khalwat qanun in Aceh Tamiang District, based on Aceh Province Qanun Number 6 of 2004 about Jinayat Law in the progressive Islamic education model. This research method is normative and empirical. It looks at legal principles and norms in laws and regulations, legal doctrine, and how legal norms are used in society. It then looks at the problem from the point of view of Acehnese scholars regarding violations of the khalwat qanun. The results of the study show that when putting customary life into practice, regions can set up different policies to help adat and traditional institutions in their areas that are based on Islamic law and work in line with it. Gampong or village residents who break the khalwat or make the Sharia look bad can first go to a Gampong Traditional Meeting (RAG). One reason why khalwat offenders aren't caned in Aceh Tamiang is because the case was settled in a way that was unfair to both local elites and the general public. A number of Khalwat cases were resolved through customary mechanisms. Sanctions such as the "banquet of bad luck," handing over tens of sacks of cement for village infrastructure development, and washing and humiliating in public places are forms of settlement for indigenous peoples. Many indigenous peoples outside Aceh also carry out sanctions like this. considerations of efficiency, expediency, and trustworthiness. Through customary mechanisms, khalwat cases are handled more quickly and efficiently than in the Sharia Court. In addition, the implementation of Qonun Jinayah can be carried out using a progressive education model approach that aims to raise awareness in every individual community about the enforcement and implementation of Qonun Jinayah in the Aceh Tamiang region.